IQTIBAS DALAM AL-QUR’AN: PENGERTIAN, MACAM DAN CONTOHNYA - Elza Muthia; Abdul Fikri (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
Iqtibas in the Qur’an is an important area of study in the fields of balaghah and Islamic literature, focusing on the use of excerpts from Qur’anic verses or hadiths in expressions, literary works, speeches, or writings with the aim of enhancing linguistic beauty and reinforcing meaning. This study aims to explain the concept of iqtibas, its forms, and its role in the linguistic study of the Qur’an. The method used is a qualitative approach employing a literature review through the analysis of various works on exegesis, rhetoric, and the sciences of the Qur’an. The results of the study indicate that iqtibas plays a significant role in reinforcing the message, providing linguistic aesthetic value, and demonstrating the depth of the author’s or speaker’s understanding of the Qur’an. Iqtibas is also categorized into several forms, including iqtibas that retains the original wording and iqtibas that undergoes minor adjustments without altering the primary meaning. In its application, scholars have established guidelines to ensure that iqtibas is conducted with full respect for the sanctity of the Qur’anic verses. Thus, studies on iqtibas not only highlight the linguistic beauty of the Qur’an but also demonstrate its far-reaching influence on the development of Islamic literature and communication.